Energising equality: The impact of globalisation on women’s empowerment in Kenya’s renewable energy sector - Laura Hellqvist; Harald Heubaum (Research in Globalization)
Globalisation has positively influenced the development and dissemination of renewable energy, particularly in developing and emerging economies. Innovation is a primary driver of such technologies and a cornerstone of the kind of global decarbonisation of energy systems needed to meet the goals of the Paris Agreement. While globalisation and technological progress drive renewable energy development, sustainable and equitable growth of the sector can only be achieved through inclusive policies and practices that address prevailing gender disparities. Globalisation may act as a double-edged sword in global development, driving economic growth and a degree of convergence between countries while simultaneously perpetuating within-country inequalities. This article explores the synergistic relationship between globalisation, renewable energy market innovations, and their socio-economic impacts on women through the lens of three energy access projects in Kenya. Despite their shared objectives of expanding energy access and fostering sustainable development, these initiatives have, at times, fallen short on their gender equality and clean, affordable energy objectives, pertaining to the debate that the benefits of globalisation are unevenly distributed, often exacerbating existing socio-economic and persistent gender disparities. Globalisation, while facilitating technological diffusion and economic growth, often fails to address the underlying inequalities that impede achieving genuine sustainable development. Lessons drawn from these projects highlight the challenges and limitations of current renewable energy access initiatives, emphasising the need to reassess strategies to better achieve the SDGs and integrate gender-sensitive policies into the broader framework of sustainable development.